The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/jcb.25987
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA MALAT‐1 Elevates HMGB1 to Promote Autophagy Resulting in Inhibition of Tumor Cell Apoptosis in Multiple Myeloma

Abstract: Long non-coding RNAs (lncRNAs) can participate in the pathological process of multiple myeloma (MM) via regulation of specific gene expression and function. This research aimed to study the role of MALAT-1 and the underlying mechanism in MM. In this study, the expression of MALAT-1 and HMGB1 protein in the bone marrow mononuclear cells from MM patients at different stages and in MM cell lines was determined by qRT-PCR and western blot, respectively. The endogenous expression of MALAT-1 and HMGB1 was modulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
79
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 25 publications
0
79
0
Order By: Relevance
“…Multiple myeloma (MM) is a kind of neoplastic plasma-cell disorder, characterized by the immersion of malignant plasma cells into bone marrow and still incurable [1,2]. The survival terms of patients with MM range from a few weeks to more than 10 years with the five-year survival rate of 40 %.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple myeloma (MM) is a kind of neoplastic plasma-cell disorder, characterized by the immersion of malignant plasma cells into bone marrow and still incurable [1,2]. The survival terms of patients with MM range from a few weeks to more than 10 years with the five-year survival rate of 40 %.…”
Section: Introductionmentioning
confidence: 99%
“…The survival terms of patients with MM range from a few weeks to more than 10 years with the five-year survival rate of 40 %. Etiologies and potential molecular mechanisms of MM are still poorly understood, which results in complicated therapies [1,3,4]. In spite of advanced progress in diagnosis and treatment, including immunomodulatory medicine, proteasome inhibitors and autologous stem cell transplantation, the prognosis of MM is also dismal.…”
Section: Introductionmentioning
confidence: 99%
“…Specially, we found that AKT2 had a somatic mutation in LGG patients; however, GBM patients did not carry any mutations on AKT2 . In addition, AKT2 interacted with lncRNA MALAT1 (ENSG00000251562), which is a famous cancer‐associated lncRNA . AKT3 interacted with lncRNA TUG1 (ENSG00000253352), which also plays an important role in various kinds of cancer .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the knockdown of MALAT1 induces apoptosis in MM cells through an endogenous apoptotic pathway by downregulating Bcl‐2 and upregulating Bax. On the other hand, MALAT1 can regulate MM cell autophagy by binding to high mobility group box 1 (HMGB1) at the post‐translational level . HMGB1 is a kind of DNA‐binding protein closely correlated to hematological malignancies, including lymphoma and MM, and contributes to the growth and proliferation of MM cells .…”
Section: Mechanisms Of Lncrnas In MMmentioning
confidence: 99%